The effect of patellar taping on EMG activity of vasti muscles during squatting in subjects with patellofemoral pain syndrome (PFPS) - Javid Mostamand; Den Al Bader; Zoee Hudson (Vesnu Publications, 2010)
Abstract   Introduction: Patellar taping has been shown to reduce pain level in subjects with patellofemoral pain syndrome (PFPS) however; the mechanisms of pain reduction have not completely been established following its application. The purpose of this study was to evaluate EMG activity of vasti during patellar taping. Materials and Methods: Both VMO-VL onset and VMO/VL amplitude of eighteen subjects with PFPS and eighteen healthy subjects as controls were measured by an EMG unit. This procedure was performed on the affected knee of subjects with PFPS, before, during and finally after patellar taping during unilateral squatting. The similar procedure was also performed on the unaffected knees of both groups. Results: The mean values of VMO-VL onset prior to taping (2.54 ms, SD 4.35 ms) were decreased significantly following a period of taping (-6.00 ms, SD 3.40 ms) (P < 0.05). There was also significant difference between the mean values of VMO-VL onset among controls (-2.03 ms, SD 6.04 ms) and subjects with PFPS prior to taping (P > 0.05). However, there were no significant difference between the ranked values of VMO/VL amplitude of affected and unaffected knees of PFPS subjects and controls during different conditions of taping (P > 0.05). Conclusion: Decreased values of VMO-VL onset may contribute to patellar realignment and explain the mechanism of pain reduction following patellar taping in subjects with PFPS. Keywords: Patellar taping, VMO & VL onset, VMO & VL amplitudes.